I'm trying to verify that: -tan^2(x) is the same as (sec^2(x)) * (-sin^2(x)) But I get: -tan^2(x) = -(sec^2(x) - 1) Where does the sin^2(x) come from?
Last edited by daigo; Jun 8th 2012 at 03:24 AM.
Follow Math Help Forum on Facebook and Google+
Originally Posted by daigo I'm trying to verify that: -tan^2(x) is the same as (sec^2(x)) * (-sin^2(x)) But I get: -tan^2(x) = -(sec^2(x) - 1) Where does the sin^2(x) come from? $\displaystyle \displaystyle \begin{align*} \sec^2{x}\left(-\sin^2{x}\right) &\equiv \frac{1}{\cos^2{x}}\left(-\sin^2{x}\right) \\ &\equiv -\frac{\sin^2{x}}{\cos^2{x}} \\ &\equiv -\tan^2{x} \end{align*}$
View Tag Cloud